Nut consumption and risk of mortality in the Physicians’ Health Study(1)(2)(3)(4) - Hshieh, Tammy T (Am J Clin Nutr, 2015)
Background: Previous studies have suggested that nut consumption is associated with beneficial cardiovascular outcomes. However, limited data are available on the association between nut intake and all-cause mortality. Objective: Our aim was to test the hypothesis that nut consumption is inversely associated with the risk of all-cause mortality. Design: In this prospective cohort study in 20,742 male physicians, we assessed nut intake between 1999 and 2002 via a food-frequency questionnaire and ascertained deaths through an endpoint committee. We used Cox regression to estimate multivariable-adjusted HRs for death according to nut consumption. In secondary analyses, we evaluated associations of nut consumption with cause-specific mortality. Results: During a mean follow-up of 9.6 y, there were 2732 deaths. The mean (±SD) age at baseline was 66.6 ± 9.3 y. Median nut consumption was 1 serving/wk. Multivariable-adjusted HRs (95% CIs) were 1.0 (reference), 0.92 (0.83, 1.01), 0.85 (0.76, 0.96), 0.86 (0.75, 0.98), and 0.74 (0.63, 0.87) for nut consumption of never or <1 serving/mo, 1–3 servings/mo, 1 serving/wk, 2–4 servings/wk, and ≥5 servings/wk, respectively (P-linear trend < 0.0001), after adjustment for age, body mass index, alcohol use, smoking, exercise, prevalent diabetes and hypertension, and intakes of energy, saturated fat, fruit and vegetables, and red meat. In a secondary analysis, results were consistent for cardiovascular disease mortality but only suggestive and non–statistically significant for coronary artery disease and cancer mortality. Conclusion: Our data are consistent with an inverse association between nut consumption and the risk of all-cause and cardiovascular disease mortality in US male physicians.